2021
DOI: 10.1111/jpn.13540
|View full text |Cite
|
Sign up to set email alerts
|

Seaweed polysaccharide mitigates intestinal barrier dysfunction induced by enterotoxigenic Escherichia coli through NF‐κB pathway suppression in porcine intestinal epithelial cells

Abstract: This study aimed to investigate the protective effects and underlying mechanism of seaweed polysaccharide (SWP) on intestinal epithelial barrier dysfunction induced by E. coli in an IPEC-J2 model. A preliminary study was done to screen optimum SWP concentrations by cell viability, cytotoxicity, apoptosis and proliferation evaluation.The regular study was conducted to evaluate the protective effects of SWP against E. coli challenge via the analysis of transepithelial electrical resistance (TEER), tight junction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 32 publications
(53 reference statements)
2
7
0
Order By: Relevance
“…Additionally, the brown seaweed extract reduced IL-6, IL-8, and TNF-α expressions in piglets with LPS-induced colitis, thereby inhibiting the pro-inflammatory factor response [ 76 ]. Consistent with the findings of other studies, we found that a dietary addition of enzymolysis seaweed powder in kittens reduced TNF-α, IL-1β, and IL-6 levels, probably by inhibiting NF-κB activation to reduce the inflammatory response [ 77 ]. Seaweed polysaccharides were reported to inhibit NF-κB activation and downregulate the mRNA expressions of TLR-4, MyD88, and IκBα, thereby inhibiting IL-6 and TNF-α expressions [ 77 ].…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, the brown seaweed extract reduced IL-6, IL-8, and TNF-α expressions in piglets with LPS-induced colitis, thereby inhibiting the pro-inflammatory factor response [ 76 ]. Consistent with the findings of other studies, we found that a dietary addition of enzymolysis seaweed powder in kittens reduced TNF-α, IL-1β, and IL-6 levels, probably by inhibiting NF-κB activation to reduce the inflammatory response [ 77 ]. Seaweed polysaccharides were reported to inhibit NF-κB activation and downregulate the mRNA expressions of TLR-4, MyD88, and IκBα, thereby inhibiting IL-6 and TNF-α expressions [ 77 ].…”
Section: Discussionsupporting
confidence: 92%
“…It might be related to the anti-inflammatory activity of arabinose, galactose and fucoidan in plant-derived polysaccharides ( Wang et al, 2023 ). In addition, in vitro experiment found the E. coli -induced intestinal barrier dysfunction was alleviated by seaweed polysaccharide supplementation via the inhibition of the NF-κB pathway ( TLR4 , MyD88 , IκBα and p65 mRNA level) and inflammatory cytokines (IL-6 and TNF-α) production of IPEC-J2 cells ( Guo et al, 2021 ). Another in vitro experiment showed that AAP significantly inhibited the production of IL-6 and TNF-α in murine RAW 264.7 macrophages stimulated by lipopolysaccharide (LPS) ( Zhang et al, 2022a ).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing studies proved that polysaccharide could modulate pro-inflammatory cytokines via regulate NF-κB-related pathways. 9,41 Furthermore, NF-κB was upregulated in AR, 17 and participated in Treg/Th17 imbalance through modulating Foxp3 expression. 18 Hence, we determined to explore the effects of NF-κB on the alleviating role of APS in AR.…”
Section: Discussionmentioning
confidence: 99%